Inverse sinusoidal pulse width modulation switched electric vehicles’ battery charger - Saurav Das; Khosru M. Salim; Dhiman Chowdhury; Mohammed Mahedi Hasan (Institute of Advanced Engineering and Science, 2019)
This paper documents an efficient, cost-effective and sustainable grid-connected electric vehicles (EVs) battery charger based on a buck converter to reduce the harmonics injected into the mains power line. To utilize the switching converter as an effective power factor controller (PFC), inverse sinusoidal pulse width modulation (ISPWM) signals have been applied. A mathematical relationship between the sending-end power factor and the duty ratio of the switching converter has been presented. To ensure the sustenance of the proposed method, a simulation model of the proposed battery charging system has been tested on PSIM simulation platform. The simulation results yield to a lossless charging system with a sending-end power factor close to unity. An experimental testbed comprising a 60 V battery bank of 100 A-h capacity with a charging current of 7 A has been generated. The laboratory assessments present an 88.1% efficient charging prototype with a resultant sending-end power factor of 0.89. The laboratory framework concerns with the comparative analysis of the power efficiency, sending-end power factor and lines current total harmonic distortion (THD) values obtained for different charging methods and the evaluations corroborate the reliability of the proposed work.